2016
DOI: 10.5664/jcsm.5598
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances in Traumatic Brain Injury: A Meta-Analysis

Abstract: Study Objectives: Sleep disturbances are frequently reported following traumatic brain injury (TBI); however, the exact disturbances remain unclear. This meta-analysis aimed to characterize sleep disturbance in community dwelling patients with TBI as compared to controls. Methods: Two investigators independently conducted a systematic search of multiple electronic databases from inception to May 27, 2015. Studies were selected if they compared sleep in community dwelling individuals with TBI relative to a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 65 publications
(141 reference statements)
2
56
1
1
Order By: Relevance
“…However, consistent with previous work, 14,16,49 the TBI group had marginally higher PSQI scores, which was driven by a significant difference in the sleep latency component of the scale (time to fall asleep; non-TBI = 1.42, TBI = 2.1; t(78) = 2.57, p = .01). The Sleep and Wake conditions did not differ based on MEQ, SSS2, or ESS scores.…”
Section: Demographic Informationsupporting
confidence: 87%
See 3 more Smart Citations
“…However, consistent with previous work, 14,16,49 the TBI group had marginally higher PSQI scores, which was driven by a significant difference in the sleep latency component of the scale (time to fall asleep; non-TBI = 1.42, TBI = 2.1; t(78) = 2.57, p = .01). The Sleep and Wake conditions did not differ based on MEQ, SSS2, or ESS scores.…”
Section: Demographic Informationsupporting
confidence: 87%
“…14,16,49 In the current sample, the difference in PSQI scores was mainly driven by the sleep latency component of the scale, which queries how long it takes the individual to fall asleep. Participants with a history of TBI reported significantly longer sleep latency.…”
Section: Sleep Quality and Architecture In Chronic Tbimentioning
confidence: 81%
See 2 more Smart Citations
“…3 In traumatic brain injury patients, subjective complaints of daytime sleepiness and poor sleep quality, as well as poorer sleep efficiency and reduced sleep time on polysomnography, are quite common. 4,5 That said, there is evidence that ubiquity of sleep disorders may not be limited to veterans of recent conflicts; in one study, 87% of older veterans, age 55-89, were found to have sleep-disordered breathing. 6 The relationships between sleep and metabolism are plausibly bidirectional and interwoven.…”
mentioning
confidence: 99%